Mean field interaction model accounting for the spatial distribution of inclusions in elastic-viscoplastic composites. (1st August 2021) - Kowalczyk-Gajewska, K.; Majewski, M.; Mercier, S.; Molinari, A.
Abstract: A cluster interaction model has been proposed to account for the spatial distribution and morphology of particles when estimating the effective properties of elastic and thermoelastic composites (Molinari and El Mouden, 1996). In the present paper this approach is extended to elastic-viscoplastic composites. To this end the tangent linearization of the non-linear viscoplastic law and the concept of additive interaction equation are used. Although the extension is formulated for the non-linear case, first applications are considered for linear viscoelastic composites, a situation rich enough to evaluate the interest of the cluster interaction approach. Results of the model are compared to numerical homogenization for periodic unit cells with two cubic configurations.